Electrocatalytic glucose oxidation on a combinatorially electrodeposited cobalt-copper-nickel thin film material library. (1st May 2020) - Pötzelberger, Isabella; Grill, Carina Daniela; Uiberlacker, Lisa Maria; Mardare, Andrei Ionut; Hild, Sabine; Hassel, Achim Walter
Abstract: A Co–Cu–Ni thin film material library was fabricated using a modified 3D-printed Hull cell. Rather than previous one by one attempts a combinatorial approach was here not to miss the exact optimum performance composition. An optimum activity at Co-16 at.% Cu-12 at.% Ni for the electrocatalytic glucose oxidation was found by screening along the compositional spread using flow-type scanning droplet cell microscopy (FT-SDCM). Crystallographic properties, surface microstructure and surface topography were investigated along the entire compositional spread using X-ray diffraction (XRD), scanning electron microscopy (SEM) as well as atomic force microscopy (AFM), respectively. The entire compositional spread (Co 40–76 at.%, Cu 0–19 at.% and Ni 11–60 at.%) showed suitability for being used in glucose detection, as determined by cyclic voltammetric measurements. A maximum response for glucose electrooxidation was identified at a Ni content of 12 at.% with a current density value of 21.8 mA cm −2 . The performance of a glucose sensor constructed using this identified thin film alloy was evaluated by localised amperometric detection. A linear behaviour was obtained for a wide range of glucose concentrations in the electrolyte solution between 1 mM and 100 mM. Additionally, the identified thin film alloy showed high stability, good electrooxidation reproducibility and high selectivity, thus indicating its suitability for being used as catalyst in glucose detection. Graphical abstract: Image 1 Highlights: Co–Cu–Ni thin film material library was fabricated in a modified 3D-printed Hull cell. Localised physical characterisation was linked to microelectrochemical methods. Optimum activity at Co-16 at.% Cu-12 at.% Ni was found for electrocatalytic glucose oxidation.